Nilai-Nilai Dalam Tradisi Bara’an: Perspektif Masyarakat Desa Kembung Baru Kecamatan Bantan Kabupaten Bengkalis - Cahyati, Fitria; Almaffaza, Muhammad; Jailani, Ahmad (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
Celebrating Eid al-Fitr after fasting in the month of Ramadan with extended family is a routine for some Indonesian people. In this Eid Al-Fitr there is a tradition that has become entrenched, namely the Bara'an Tradition. Bara'an is the right moment to stay in touch and apologize to one another. Bara'an is also considered as a place for productive communication between various components of the nation which is carried out with joy and is formed ceremonially followed by a group of citizens from various religions, races and ethnicities. The purpose of this research is to find out the values ​​in the Baraan Tradition. To answer this question, this research uses descriptive qualitative methods. Because using descriptive qualitative methods, the authors examine the values ​​of the Baraan tradition with data collection techniques through observation and interviews with the people of Kembung Luar Village, Bantan District, Bengkalis Regency. The results of the interviews can be concluded that the values ​​contained in the bara'an tradition are the Value of Compassion, the Value of Happiness, the Value of Blessing, the Value of Religion, the Value of Social